Determination and correlation of solid-liquid phase equilibrium and phase diagram for multicomponent system of mixed dibasic acids. (IV) Quaternary system of (adipic acid + succinic acid + glutaric acid + ethanol). (July 2017) - Li, Xinbao; Wang, Mingju; Du, Cunbin; Cong, Yang; Zhao, Hongkun
Graphical abstract: Highlights: Solubility for quaternary system of adipic acid + succinic acid + glutaric acid + ethanol were determined. The quaternary phase diagrams were constructed at three temperatures according to the Jãneck method. The quaternary solid-liquid phase equilibrium was calculated by Wilson and NRTL models. Abstract: Solid-liquid phase equilibrium and solubility for the quaternary system of (adipic acid + succinic acid + glutaric acid + ethanol) at (283.15, 303.15, and 313.15) K were determined by using an isothermal saturation method under atmosphere pressure (101.2 kPa). Based on the determined mutual solubility, the quaternary phase diagrams were constructed at the studied temperatures according to the Jãneck method. At each temperature, the quaternary phase diagram included three crystallization regions of pure solid, three co-saturated curves and one eutectic point. The three pure solids corresponded to pure adipic acid, pure succinic acid and pure glutaric acid, which were confirmed by Schreinemaker's method of wet residue and X-ray powder diffraction. At the same temperature, the crystallization regions of succinic acid and adipic acid are larger than that of glutaric acid. Furthermore, the quaternary solid-liquid phase equilibrium was calculated by using the Wilson and NRTL models. The calculated quaternary phase diagrams agreed well with experimental results. The values of RMSD were 2.46 and 1.08 for Wilson model and NRTL model, respectively. The solid-liquid equilibrium phase diagrams and the thermodynamic models for the quaternary system could provide the fundamental basis for the separation process of a specific dibasic acid from its mixtures via solvent crystallization.